Early kidney transplantation improves neurocognitive outcome in patients with severe congenital chronic kidney disease. (13th January 2015) - Hartmann, Hans; Hawellek, Nicola; Wedekin, Mirja; Vogel, Charlotte; Das, Anibh M.; Balonwu, Katharina; Ehrich, Jochen H. H.; Haffner, Dieter; Pape, Lars
Summary: Renal replacement therapy has become available for the majority of patients suffering from severe congenital chronic kidney disease (CKD). Data on the long‐term neurocognitive outcome and the impact of early kidney transplantation (KTx) in this setting is unclear. Neurocognitive outcomes in 15 patients (11 male) with isolated congenital CKD (stage 3–5) requiring KTx at a mean age of 2.8 ± 1.3 were assessed at a mean age of 8.3 ± 1.4 years. Patients underwent neurological examination and testing for neuromotor and neurocognitive function using three independent tests. Pre‐emptive KTx was performed in six patients, and nine patients were dialyzed prior to KTx for a mean period of 11.1 ± 8.6 months. Neuromotor function was abnormal in 8/15 patients. HAWIK‐III showed a global intelligence quotient (IQ) of 93.5 ± 11.4 ( P  = 0.05) due to a significantly reduced performance IQ of 89.1 ± 11.3 ( P  < 0.01). In three patients, the global IQ was clinically significantly reduced by >1 SD to <85. In patients with neuromotor dysfunction, performance IQ was lower than in patients with normal neuromotor function (83.8 ± 10.2 vs. 96.2 ± 9.0, P  = 0.04). Time on dialysis was inversely correlated to verbal IQ ( r  = 0.78, P  = 0.02). Pre‐emptive KTx and duration of dialysis treatment <3 months was associated with superior neurocognitive outcome. Early (pre‐emptive) KTx results in superior long‐term neurocognitive outcome in children with severe congenital CKD.